Analysis of the impact of distributed generation on grounding method of distribution network. Issue 13 (4th December 2017) - Qian, Wang; Jun, Lu; Jiandong, Duan; Wangjing, Tan
Abstract : As more and more distributed generation (DG) access to distribution network, the study of the impact of DG on distribution network becomes an important issue. When DG units are introduced in distribution systems, the power network structure had changed, it will influence the original grounding method of the distribution network; so, it is necessary to analyse the effect of DG connecting on distribution network. Here, for different operation characteristics of DG, a simulation model of DG connecting to 10 kV distribution network has established, and the simulation results of DG with different grounding method connected to distribution network have obtained. The results showed that ungrounded DG connected to distribution network has little effect on the original grounding method of distribution network, but the low‐resistance grounding DG and grounded DG connected to distribution network have impact on the original grounding method of distribution network. So, DG has to be considered an important factor when selecting the neutral grounding model of distribution network.